PENGARUH KONSENTRASI P. polymyxa DAN DOSIS PUPUK NITROGEN TERHADAP INTENSITAS SERANGAN PENYAKIT BLAS (Pyricularia oryzea) PADA TANAMAN PADI (Oryza sativaL.) - Endang Suprapti; Agus Budiyono; Tanto Harto (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
Rice is the main food crop commodity in Indonesia. However, in the process of cultivation there are obstacles that can reduce the level of productivity. One of the obstacles is the presence of pest attack one of them attacks blas disease (Pyricularia oryza). One of the causes is excessive nitrogen fertilization. One of the factors that can suppress the development of this disease is by application of P. polymyxa. This is the underlying title of this study. This study aims to determine the effect of P. polymyxa concentration and dose of nitrogen fertilizer on the intensity of blast disease (Pyricularia oryzea) in rice plants (Oryza sativa L.). This research was conducted in February - June 2017, where research Kebumen, Banyubiru, Semarang at altitude of place 478 m. The method used in this research is factorial method with RAKL pattern consists of 2 treatment factors and 3 repetitions. The first factor is the concentration of P. polymyxa (P) consisting of 4 levels ie concentration 0, 5, 10 and 15 cc / liter (P0, P1, P2 and P3) and the second factor is the dosage of nitrogen fertilizer (N) ie dose 45, 90 and 135 kg / ha (K0, K1, K2 and K3). The results showed that interaction between P. polymyxa concentration and nitrogen dose gave a very real effect on the intensity parameter of leaf blast attack and number of tillers but gave a real effect on the intensity parameter of neck blast attack, plant height, number of grain of hollow per panicle, and per hectare, number of permedional grains, wet stalks, dry stover, productive shoots, panicle length, number of grains per panicle and weight per 1000 seeds. The best treatment in the study of the effect of P. polymyxa concentration and the dose of nitrogen fertilizer on the intensity of blast disease (Pyricularia oryzea) in rice plants (Oryza sativa L.) was P2N2 (P. polymyxa 10 cc / liter with nitrogen dose of 90 kg / ha) .